LAJU PRODUKTIFITAS BIOMASSA DAUN Halodule uninervis PADANG LAMUN PULAU DERAWAN - Roem, Muhamad (Jurnal Harpodon Borneo, 2013)
The aim of the research is to analize the leaf biomass productivity rate of Halodule uninervis. The research conducted in seagrass meadows of Derawan Island. The research method was a combination of ecological survey and field experiment. The result of the research shows that Derawan meadows dominated by H. Uninervis that made up to 86 % contribution to total relative density. H. Uninervis with average density 3.576 ± 115 ind m -2 has daily leaf productivity value 0,32 ± 0.03 g DW m -2 day -1.Key Words : carrying capacity, seagrass meadows, foraging habitat, green seaturtle, species shifting, ecological sustainability.